Isolation and Identification of Salmonella typhimurium in an Umbilical Area from Chicks in Kerbala City - Mustafa Mahmood NaemaAl-taeeand; Sahar Mahdi Hayyawi Al-Rubay (Institute of Medico-legal Publications Pvt Ltd, 2022)
One hundred samples ofumbilicus were taken from chicks .Out of these, 27 (27%) were positive.The most common of bacterial isolates were Salmonella typhimurium. The biochemical tests for allisolates, whether from chicks, showed a positive test to check the production of hydrogen sulfide gas,the fermentation of glucose sugar, the use of citrate as a source of carbon, non-lactose fermentedandnegative for urease enzyme, the result found the most common infection in the cold weather February, they were found nine isolates (33.33%) more than other groups as 29.63%, 14.82 %and 11.11%,for January , November , December and October , respectively. The resultswere found a total of 27isolates were Salmonella spp., on the other hand 11 isolates wereidentified as Salmonella typhimurium(40.74%) by Vitek 2 compact system, , All Salmonella spp. showed high susceptibility againstNitrofurantoin, 27 (100%) and ciprofloxacin24 (88.8%), whereas they were highly resistance againstAmoxicillinCefotaxime, and Vancomycin 24 (88.8% ).. Chicks with umbilical area were found toharbor different pathogens and they are considered a source of infection during successive days in thelife of broilers chickens.